Application and Influencing Factors of Radiofrequency Ablation in Monochorionic Pregnancy. Issue 4 (8th October 2022) - Pan, Pingshan; Huang, Dongbing; Tang, Lu; Yang, Zuojian; Qin, Guican; Wei, Hongwei
Abstract: Objective: The aim of the study was to investigate the pregnancy outcomes and possible influencing factors concerning complicated monochorionic (MC) multiple pregnancies undergoing selective fetal reduction using radiofrequency ablation (RFA). Methods: This retrospective cohort study included 54 women with complicated MC multiple pregnancy who underwent selective fetal reduction using RFA at the Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region from January 2015 to March 2020. According to the indications for RFA, the 54 women were divided into three groups: complex complications ( n = 30), structural anomalies ( n = 18), and triplet pregnancy ( n = 6). According to the gestational age for RFA, all patients were divided into three groups: 16–19 +6 weeks ( n = 17), 20–23 +6 weeks ( n = 17), and 24–26 +6 weeks ( n = 20). We analyzed the pregnancy outcomes (including the overall survival rate (OSR), gestational age at delivery, birth weight of newborns) and postoperative complications such as miscarriage, and intrauterine fetal death (IUFD) according to the indications and gestational age of reduction by using suitable statistical testing. Results: The OSR was 83.3% (45/54). The mean ± standard deviation ( SD ) of gestation at the time of reduction was 21.6 ± 3.2 weeks. The GA at delivery was 34.0(32.0, 37.5) weeks. The mean ± SD of newborns' birth weight was 2118 ± 685 g. The overall rates of miscarriage, PROM, and IUFD were 9.3% (5/54), 7.4% (4/54), and 7.4% (4/54), respectively. According to the indications for reduction, the OSR for complex complications, structural anomalies, and triplet pregnancy groups were 83.3% (25/30), 83.3% (15/18), and 83.3% (5/6), respectively. Statistically significant differences were only found in the mean birth weight among the three groups ( P < 0.05). No significant difference was found in the rate of miscarriage, and mean gestation at delivery among the three groups ( P > 0.05). In the group with complex complications, the OSR of twin-to-twin transfusion syndrome, selective intrauterine growth restriction, twin reversed arterial perfusion sequence, and twin anemia polycythemia sequence were 66.7% (6/9), 93.3% (14/15), 80.0% (4/5), and 100.0% (1/1), respectively, with no significant difference among these groups ( P > 0.05). According to the gestational age of reduction, the OSRs among the three groups were 82.4% (14/17), 76.5% (13/17), and 90.0% (18/20), respectively, and the rate of miscarriage, IUFD, and mean gestation age at delivery among these groups showed no significant difference ( P > 0.05). Conclusion: Selective fetal reduction by RFA is an important treatment method for complicated MC multiple pregnancy, although it may lead to complications like miscarriage, and IUFD. The indication of reduction seems to affect the pregnancy outcome. An optimal treatment plan should be selected according to the patient's conditions in clinical practice.